2016
DOI: 10.1007/s11120-016-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

Drought-induced changes in photosynthetic apparatus and antioxidant components of wheat (Triticum durum Desf.) varieties

Abstract: Water deficit is a key factor influencing the yield and quality of crops. In the present study, the photosynthetic responses by means of chlorophyll fluorescence of chloroplasts, thylakoid membrane proteins, and antioxidant components were analyzed in wheat (Triticum durum Desf.) plants differing in their tolerance to drought. Two durum winter wheat varieties, Barakatli 95 (drought tolerant) and Garagylchyg 2 (drought sensitive) were grown under field well-watered and drought conditions. It was found that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Plant. 167, 2019 (Huseynova et al 2016). This shows that the TH proteins are critical in plants response to various abiotic stresses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Plant. 167, 2019 (Huseynova et al 2016). This shows that the TH proteins are critical in plants response to various abiotic stresses.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, hydrophilic proteins have also been found to be important in reducing the amount of oxidants produced within the plant cells during stressful conditions. Abiotic stress such as drought triggers a wide variety of plant responses, including alterations in gene expression, the accumulation of metabolites such as the phytohormone ABA or osmotically active compounds, and the synthesis of specific proteins, especially hydrophilic proteins scavenging the oxygen radicals released by the plants (Huseynova et al ). This shows that the TH proteins are critical in plants response to various abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that photosynthesis during grain filling stage contributes approximately 70–90% of photo-assimilates to the final grain yield under the favorable conditions ( Austin et al, 1977 ; Bidinger et al, 1977 ), while post-anthesis photosynthates are highly susceptible to drought ( Huseynova et al, 2016 ). Drought stress significantly restricts photosynthesis through stomatal limitation or non-stomatal limitation ( Caemmerer and Farquhar, 1981 ; Lawlor and Tezara, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress happened during grain filling could reduce wheat yield significantly, while drought tolerant varieties could maintain lower grain yield loss than the drought sensitive varieties ( Saeedipour and Moradi, 2011 ). Such yield loss was largely due to the inhibition of photosynthesis under drought ( Austin et al, 1977 ; Huseynova et al, 2016 ). The inhibition of plant photosynthesis may be resulted from the stomatal and/or non-stomatal limitation, which depended on the severity of drought stress ( Caemmerer and Farquhar, 1981 ; Lawlor and Tezara, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drought is one of the dominant natural hazards that negatively affect dry mass accumulation, respiration rate, and wheat productivity (Huseynova et al 2016). We chose local varieties Gobustan and Tale 38, which are productive and at the same time contrasting in their drought tolerance, as the objects of the study because of the increased attention paid to the cultivation of bread wheat varieties in these areas.…”
Section: Introductionmentioning
confidence: 99%